'Complex Political Victims' in the Aftermath of Mass Atrocity: Reflections on the Khmer Rouge Tribunal in Cambodia. (13th November 2015) - Bernath, Julie
ABSTRACT 1 : Reflecting on the case study of the Extraordinary Chambers in the Courts of Cambodia (ECCC), this article asks how transitional justice (TJ) processes account for the complexity of victimhood in political violence and mass atrocity. It speaks to the critical scholarship which questions the use of simplistic dichotomies of (innocent) victims versus (guilty) perpetrators in TJ processes. Findings from empirical, qualitative fieldwork conducted in 2013 and 2014 show that both inclusion and exclusion dynamics towards complex political victims take place at the ECCC. Whilst most critical scholarship questions the exclusion of complex political victims from TJ processes, this article highlights the limitations and challenges of both the inclusion and the exclusion of such victims. It argues that the complexity of victimhood in contexts of mass atrocity poses vexing questions to TJ scholars and practitioners that have yet to be addressed.